2013
DOI: 10.1177/1933719112468956
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Binding Cassette Transporter A1 Expression Is Decreased in Preeclamptic Placentas

Abstract: Preeclampsia is a pregnancy-specific multisystem disorder characterized by hypertension and proteinuria. Accentuated maternal hyperlipidemia, especially high serum levels of oxidized low-density lipoprotein (oxLDL), is one of the features of preeclampsia. We previously reported that lectin-like oxidized LDL receptor 1 (LOX-1) expression was decreased in preeclamptic placentas. Here, we show that decreased LOX-1 expression is associated with low expression of adenosine triphosphate-binding cassette transporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Consistent with previous studies in humans [ 19 , 20 , 22 ], placental ABCA1 expressions were decreased in the COMT −/− mice model of PE. The ABC transporters comprise a family of functionally diverse polytopic transmembrane proteins and are able to translocate a wide variety of substrates, including amino acids, lipids, ions, peptides and drugs, across extracellular and intracellular biological membranes [ 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies in humans [ 19 , 20 , 22 ], placental ABCA1 expressions were decreased in the COMT −/− mice model of PE. The ABC transporters comprise a family of functionally diverse polytopic transmembrane proteins and are able to translocate a wide variety of substrates, including amino acids, lipids, ions, peptides and drugs, across extracellular and intracellular biological membranes [ 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…In a subsequent study, the same group also showed that the decreased LOX-1 expression could lead to insufficient uptake of Ox-LDL and subsequently leading to decreased LXR activation and thereby decreasing ABCA1 expression. These findings indicate that ABCA1 expression is decreased in preclamptic placentae and also provides new insights in understanding pathophysiology of preeclampsia (35). However, these results are different with those reported by Plosch et al, indicating an upregulation of ABCA1 in early onset preeclamptic placentae but not significant elevation in late onset preeclampsia (32).…”
Section: Abc Transporters In the Placentamentioning
confidence: 68%
“…In addition, preeclampsia affects the long-term outcome of both mothers and their offspring ( Bokslag et al, 2016 ). Serum levels of triglycerides, LDLs, small dense LDLs that are susceptible to oxidation, as well as oxLDLs are higher in women with preeclampsia compared to healthy pregnant women ( Chigusa et al, 2013 ). Murata et al (1996) found decreased expression of VLDLR and LDLR mRNA in third trimester placentas derived from preeclamptic women.…”
Section: Cholesterolmentioning
confidence: 99%
“…Thus, the LXR-mediated upregulation of ABC-transporters in GDM appeared to restore cholesterol homeostasis ( Sun et al, 2018 ). Alterations of expression levels of ABCA1 and ABCG1 in total placental tissue in case of pregnancy diseases such as GDM, preeclampsia, hypoxia, or antiphospholipid-syndrome were reported, but the results are partly inconsistent ( Albrecht et al, 2007 ; Plosch et al, 2007 , 2010 ; Korner et al, 2012 ; Baumann et al, 2013 ; Chigusa et al, 2013 ; Dube et al, 2013 ; Liu et al, 2014 ; Huang et al, 2018 ).…”
Section: Cholesterolmentioning
confidence: 99%